Preparation and Properties of a Hydrolytically Stable Cyclooctyne-Containing Polymer - Li, Kelvin; McNelles, Stuart A.; Adronov, Alex (Synlett, 2018)
A poly[(phenylene vinylene)-co-dibenzocyclooctyne] polymer prepared by Wittig polymerization chemistry between dibenzocyclooctyne bisaldehyde [DIBO-(CHO)2] and bis(triethyleneglycol)phenylbis(tributylphosphonium) dibromide is reported. The resulting polymer exhibits moderate molecular weight (Mn: 10.5 kDa, Mw: 21.3 kDa, Ð: 2.02) and is fluorescent. It could be readily functionalized by strain-promoted alkyne-azide cycloadditon with different azides, and fluorescence of the polymer was preserved after functionalization. Grafting azide-terminated 5 kDa poly(ethylene glycol) monomethyl ether chains drastically affected the solubility of the polymer. Cross-linking the polymer with poly(ethylene glycol) that was terminated at both ends with azide groups gave access to a fluorescent organogel that could be dried and reswollen with water to form a hydrogel.
Keywords: Wittig reaction; cycloaddition; cyclooctyne; conjugated polymer; polymer functionalization; cross-linking